Mekanisme Penggetasan Baja Karbon Rendah Pada Berbagai Tingkat Neutron Fluen = (The Embrittlement Mechanism Of Low Carbon Steel Atarious Neutron Fluent) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Low carbon steel is used as nuclear reactor core vessel material. Its superior mechanical and nuclear properties at low neutron flux are the main reason for using it as a nuclear reactor vessel material. At the neutron fluent of 3.1013 n/cm2 the embrittlement mechanism becomes significant to observe especially, throughout the usage in nuclear reactor. In this research are used activation, mechanical testing (tensile test) and diffiaction metallography. (TEM) methods, Low carbon steel was irradiated at the neutron fluent of 9.101' n/cm2, 1,8.1016 n/cm2, 2,4.1016 n/cm2. In annealing condition the mechanical properties of low carbon steel are the ultimate strength (o-â) = 93.740 psi and the yield streength (cry) = 54.500 psi. At irradiated conditions the mechanical properties of low carbon steel are 0